The Effect of the Abbasids’ Political Disintegration on the Architectural Development of the Prophet’s Mosque - Spahic Omer (Al-Jami'ah: Journal of Islamic Studies, 2016)
This article discusses the contributions of the Abbasid caliphs to the architectural development of the Prophet’s Mosque in Madinah. Those contributions began almost as early as the Abbasid caliphal government had officially emerged as the successor to the Umayyads, and ended with a major rebuilding and renovation work in 887 AH/1482 CE, about 35 years before the ultimate dissolution of the Abbasid regime. The last work was executed by the Mamluk rulers as the Abbasid proxies. The paper focuses on discussing the consequences and implications of a political disintegration during the Abbasid era for the architectural development and serviceability of the mosque. The article concludes that the Abbasid contributions to the architectural development of the Mosque were rather inadequate. The blame is to be attributed partly to the Abbasids themselves and partly to the prevalent circumstances in the state that eventually incapacitated the Abbasid government from performing its entrusted duties and responsibilities. However, even for the creation and fostering of the latter, it was again the Abbasids who more than anybody else are to be held accountable.[Artikel ini membahas peran para khalifah Abbasiyah dalam pengembangan arsitektur Masjid Nabawi di Madinah. Kontribusi mereka dimulai sejak awal pemerintahan Abbasiyah muncul sebagai penerus Umayyah dan berakhir dengan renovasi besar pada 887 H/1482 M, sekitar tiga dasawarsa menjelang berakhirnya pemerintahan Abbasiyah di Mesir. Pekerjaan terakhir dilakukan oleh penguasa Mamluk sebagai wakil Dinasti Abbasiyah. Fokus makalah ini adalah konsekuensi dan implikasi dari disintegrasi politik selama era Abbasiyah terhadap pengembangan arsitektur dan fumgsi Masjid Nabawi. Artikel ini menyimpulkan bahwa kontribusi Dinasti Abbasiyah untuk pengembangan arsitektur Masjid Nabawi kurang memadai, sebagai cerminan ketidakmampuan para khalifah Abbasiyah menjalankan peran, fungsi, dan tanggung jawabnya. Bahkan sebenarnya dalam renovasi yang terakhir pun, orang lain yang bertanggung jawab.]